Nutritional practices associated with low energy availability in Division I female soccer players - Reed, J. L.; De Souza, M. J.; Kindler, J. M.; Williams, N. I. (Journal of Sports Sciences, 2014)
The purpose of this study was to examine macronutrient intake, energy density and energy intake distribution that may be associated with low energy availability (EA) in Division I female soccer players. The energy intake, exercise energy expenditure and EA of 19 participants (18-21 years) was assessed during the pre-, mid- and postseasons. Repeated measures analysis of variance was performed to examine the changes across the season. Chi-square analysis was performed to examine the distribution of participants meeting the American College of Sports Medicine recommendations for carbohydrate and protein consumption. Independent t-tests were used to compare differences between groups. The proportion of athletes who did not meet the American College of Sports Medicine recommendations for carbohydrate intake (6-10 g/kg BW) was significantly greater in the low (<30 kcal/kg LBM) than higher (=30 kcal/kg LBM) EA group (?2 (1) = 7.5; P = 0.006). Participants with low compared to higher EA consumed a lower energy dense dinner (0.8 ± 0.1 vs. 1.4 ± 0.1 kcal/g; P = 0.004) after a soccer match during midseason. No differences in the percentage (%) of kilocalories from food (84.5 ± 2.0% vs. 84.7 ± 2.6%), sports drinks (7.3 ± 1.4% vs. 6.0 ± 3.2%), other drinks (7.6 ± 1.5 % vs. 6.0 ± 1.5%) or bars/gels/beans (1.7 ± 0.6 vs. 3.0 ± 1.5) were observed in participants with low compared to higher EA (P > 0.05) during the pre- and midseasons. Identifying inadequate carbohydrate intake and the practice of consuming lower energy dense meals may be important in preventing low EA conditions and consequently the Female Athlete Triad.